Античката уметничка вдаховеност и исихастичкото просветлување - Ноневски, Вангел (Филозофски факултет, УКИМ, Скопје, 2020)
The text seeks to draw a parallel between Plato’s theory of inspiration and enthusiasm in the understanding of poetic creation and the practices of enlightenment in Isihastic Orthodox Christianity, in the way that they were elaborated by the professor of ancient, medieval and Byzantine philosophy Vera Georgieva. It also elaborates some contemporary implications of both themes in the area of popular music, namely, the ways in which psychedelic experiences in rock and roll and techno music evoke enlightenment experiences. The conclusion is that the Orthodox mystical approach of Isihazm leads to a direct union with god, while the approach of divine and/or psychedelic artistic inspiration can only bring us closer to that unity. However, that closeness can never be fully realized.
Keywords: enlightenment, Isihazm, popular music, artistic inspiration, mediation